Solution!! (√3 + 1)/(2√2 – √3) Expand the expression by multiplying. = (√3 + 1)/(2√2 – √3) × (2√2 + √3)/(2√2 + √3) = [(√3 + 1)(2√2 + √3)]/[2√2 – √3)(2√2 + √3)] Simplify the denominator by using (a – b)(a + b) = a² – b². = [(√3 + 1)(2√2 + √3)]/[(2√2)² – (√3)²] = [(√3 + 1)(2√2 + √3)]/[8 – 3] = [(√3 + 1)(2√2 + √3)]/5 Multiplying the expressions in the numerator. = (2√6 + 3 + 2√2 + √3)/5 Hence, we have got our answer after rationalising the denominator and simplifying the expressions. Reply

Answer: Given √3+1/√3-1 We need to rationalize the givenequation To rationalize we will multiply and divide the denominator by √3+1 (√3+1)√3+1)/(√3-1)(√3+1) Denominator can be simplified using the identity (a2-b2)=(a-b)(a+b) And the equation becomes =(√3+1)2/(√3)2-(1)2 =(4+2√3)/2 =2+√3 Step-by-step explanation: Reply

## Solution!!

(√3 + 1)/(2√2 – √3)

Expand the expression by multiplying.

= (√3 + 1)/(2√2 – √3) × (2√2 + √3)/(2√2 + √3)

= [(√3 + 1)(2√2 + √3)]/[2√2 – √3)(2√2 + √3)]

Simplify the denominator by using (a – b)(a + b) = a² – b².

= [(√3 + 1)(2√2 + √3)]/[(2√2)² – (√3)²]

= [(√3 + 1)(2√2 + √3)]/[8 – 3]

= [(√3 + 1)(2√2 + √3)]/5

Multiplying the expressions in the numerator.

= (2√6 + 3 + 2√2 + √3)/5Hence, we have got our answer after rationalising the denominator and simplifying the expressions.

Answer:Given √3+1/√3-1

We need to rationalize the givenequation

To rationalize we will multiply and divide the denominator by √3+1

(√3+1)√3+1)/(√3-1)(√3+1)

Denominator can be simplified using the identity (a2-b2)=(a-b)(a+b)

And the equation becomes

=(√3+1)2/(√3)2-(1)2

=(4+2√3)/2

=2+√3

Step-by-step explanation: